Discordant distortion in cubic GeMnTe₂ and high thermoelectric properties of GeMnTe₂‑x%SbTe - Dong, Jinfeng (2023)
GeMnTe2 adopts a cubic rock salt structure and is a promising mid-temperature thermoelectric material. The pair distribution function analysis of neutron total scattering data, however, indicates that GeMnTe2 is locally distorted from the ideal rock salt structure with Ge2+ cations being discordant and displaced ∼0.3 Å off the octahedron center. By alloying GeMnTe2 with SbTe, the carrier concentration can be tuned in GeMnTe2-x%SbTe (x = 15.1), leading to converged multiple broad valence bands and a high Seebeck coefficient of >200 μV K−1 from 300 to 823 K. The system exhibits a large density-of-state effective mass of >10 me and a high weighted mobility of 80 cm2 V−1 s−1, leading to a power factor of 15 μWcm−1 K−2 at 823 K. The composition GeMnTe2-15.1%SbTe exhibits very low lattice thermal conductivity of ∼0.5 Wm−1 K−1 at 823 K, attributed to the combination of oX-centering cations in the rock salt structure, Ge/Mn positional disorder, dislocations, and abundant Ge-rich and Mn-rich nanoparticles. A ZT value of ∼1.5 can be achieved for GeMnTe2-15.1%SbTe with a ZTave of 0.96 in the temperature range of 400−823 K.